2008
DOI: 10.1371/journal.ppat.1000116
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-Rich Glycoprotein Protects from Systemic Candida Infection

Abstract: Fungi, such as Candida spp., are commonly found on the skin and at mucosal surfaces. Yet, they rarely cause invasive infections in immunocompetent individuals, an observation reflecting the ability of our innate immune system to control potentially invasive microbes found at biological boundaries. Antimicrobial proteins and peptides are becoming increasingly recognized as important effectors of innate immunity. This is illustrated further by the present investigation, demonstrating a novel antifungal role of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 58 publications
6
87
0
Order By: Relevance
“…The presently disclosed direct antibacterial action of C-terminal peptides of TFPI is in line with observations indicating that heparin-binding proteins, such as complement C3 (25), kininogen (36,37), heparin-binding protein (38), heparin-binding epidermal growth factor and other growth factors (39), heparin/heparan sulfate-interacting protein (40), ␤2-glycoprotein (41), histidine-rich glycoprotein (42), and human thrombin (43) may, either as holoproteins or after fragmentation, exert antimicrobial activities in vitro and, in several cases, in vivo (36,37,42). In addition, peptide-mediated C3a generation, along with enhanced MAC formation, represents a mechanism by which a host defense peptide may selectively enhance microbial killing by generation of additional complement-derived AMPs.…”
Section: Discussionsupporting
confidence: 81%
“…The presently disclosed direct antibacterial action of C-terminal peptides of TFPI is in line with observations indicating that heparin-binding proteins, such as complement C3 (25), kininogen (36,37), heparin-binding protein (38), heparin-binding epidermal growth factor and other growth factors (39), heparin/heparan sulfate-interacting protein (40), ␤2-glycoprotein (41), histidine-rich glycoprotein (42), and human thrombin (43) may, either as holoproteins or after fragmentation, exert antimicrobial activities in vitro and, in several cases, in vivo (36,37,42). In addition, peptide-mediated C3a generation, along with enhanced MAC formation, represents a mechanism by which a host defense peptide may selectively enhance microbial killing by generation of additional complement-derived AMPs.…”
Section: Discussionsupporting
confidence: 81%
“…12 Furthermore, because the binding of ␤ 2 GPI to apoptotic cells via anionic phospholipids has been proposed to initiate the break of tolerance and induce the generation of anti-␤ 2 GPI or antiphospholipid-␤ 2 GPI complex autoantibodies, 46 the interaction between HRG and phospholipids in necrotic cells may provide a potential mechanism for generating anti-HRG autoantibodies, as suggested by Ball-Rosen et al 29 In addition to regulating coagulation and fibrinolysis, HRG has also been shown to bind to and facilitate the removal of bacteria 47,48 and fungi. 49 The specific binding of HRG to pathogens [47][48][49] and molecular structures exposed on necrotic cells, as shown in this study, clearly highlights its ability to function as a PRM like C1q, CRP, MBL, and ␤ 2 GPI. Interestingly, these PRMs, including HRG, are frequently targeted by autoantibodies.…”
Section: Discussionsupporting
confidence: 51%
“…Further, in contrast to the helical and antimicrobial LL-37 (31) and C-terminal thrombin peptides (12), found to be released from their holoproteins hCAP18 and thrombin, respectively, the herein described HCIIa form per se mediates the bactericidal and LPS-binding effects. In this perspective, the molecule therefore belongs to the class of larger antimicrobial proteins such as antimicrobial RNases (32), eosinophil cationic protein (33), lactoferrin (34), PCI (29), and histidine-rich glycoprotein (35), which all exert bactericidal effects, albeit without the need for the critical and unique enzymatic activation, followed by the dramatic shift in net charge, and the shape transition observed for HCII in this work.…”
Section: Discussionmentioning
confidence: 92%